2009
DOI: 10.1111/j.1439-0523.2009.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-sexual cycle regrowth and grain yield inThinopyrum elongatum × Triticum aestivumamphiploids

Abstract: Perennial wheat is emerging as a potential long-term response to agroecological problems resulting from soil erosion. We conducted field scale trials of 31 F 5 (2005-2006) and five F 6 (2006-2007) amphiploid breeding lines derived from Thinopyrum elongatum/Triticum aestivum (cv. ÔChinese SpringÕ)//T. aestivum (cv. ÔMadsenÕ) crosses. Here, we report results on post-sexual cycle regrowth (PSCR) and grain yield in the amphiploid lines and two annual wheat cultivars from three locations in Washington State, USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Disease resistance is another key objective of some perennial grain plant breeders (Cox et al, 2005). There is one report that highlights the characteristics of the grain and grain quality in novel perennial wheat lines (Murphy et al, 2009), and perennial regrowth vigor (Murphy et al, 2010), but there are few reported efforts in these areas. The results of this study imply that breeders may wish to consider developing multiple growth forms of perennial grains to address novel market niches, and that not all of these forms may need to be yield-competitive with annual grains in order for farmers to find them desirable (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease resistance is another key objective of some perennial grain plant breeders (Cox et al, 2005). There is one report that highlights the characteristics of the grain and grain quality in novel perennial wheat lines (Murphy et al, 2009), and perennial regrowth vigor (Murphy et al, 2010), but there are few reported efforts in these areas. The results of this study imply that breeders may wish to consider developing multiple growth forms of perennial grains to address novel market niches, and that not all of these forms may need to be yield-competitive with annual grains in order for farmers to find them desirable (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although plant breeding efforts over many decades have addressed multiple simultaneous objectives, these have almost always had yield as a primary focus (Glover et al, 2010). Recent efforts to develop perennial wheat and perennial rye involve crossing of annual wheat and rye with wild relatives and selecting for improved grain yield (Acharya et al, 2004;Murphy et al, 2010). Intermediate wheatgrass is currently being domesticated through selection for high yield (Cox et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the few studies reporting the seed yields of perennial grain crops subjected to artificial selection, Scheinost et al 278 observed that promising lines of perennial wheat produced 1.7-5.8 Mg ha − 1 , as compared with 9.0 Mg ha − 1 from an annual wheat cultivar commonly grown in the area. Murphy et al 279 reported that amphiploid breeding lines derived from crosses between annual wheat and the perennial wheatgrass species Thinopyrum elongatum produced mean grain yields of 0.6-2.2 Mg ha − 1 , depending on location, which were about 44% of the seed yield of annual wheat grown at the locations. It remains to be learned how much improvement in perennial grain yields can be realized through breeding.…”
Section: Grain Cropsmentioning
confidence: 99%
“…Partly, but not entirely, because of increased demand from the bioenergy sector for commodity crops, livestock feed costs and food prices for consumers jumped upward in 2006-2007 and may in the future impose financial and nutritional burdens on low-income people in both developed and developing countries 281 . Increased crop prices may also spur conversion of land currently in perennial vegetation to arable cropland, with attendant increases in N emissions to water supplies 279 and greenhouse gas emissions to the atmosphere 149,282,283 . Increasing attention to the development of thermochemical and biochemical technologies for converting lignocellulosic materials into liquid fuels and other industrial chemicals adds new twists to the biofuels story.…”
Section: Biofuel Cropsmentioning
confidence: 99%